Application of electrolyte containing xylenol orange tetrasodium salt in preparation of aqueous zinc ion battery

By adding an appropriate amount of dicresol orange tetrasodium salt and soluble zinc salt to the electrolyte of an aqueous zinc ion battery, the problem of low battery stability caused by zinc dendrites is solved, and the battery's long life cycle under different current densities is achieved.

CN119674278APending Publication Date: 2025-03-21SHAANXI SCI TECH UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411886426.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The growth of zinc dendrites in aqueous zinc ion batteries leads to low battery stability, and the prior art is difficult to effectively inhibit its growth.

Method used

An electrolyte containing dicresol orange tetrasodium salt and soluble zinc salt was used. The concentration of dicresol orange tetrasodium salt was 0.5-2mmol/L and the concentration of zinc salt was 1.5-2.5mol/L to inhibit the growth of zinc dendrites and improve the stability of the battery.

Benefits of technology

At the current density of 1mAcm-2, the battery can cycle for more than 4000 hours; at the current density of 5mAcm-2, the battery can cycle for more than 1000 hours, significantly improving the stability of the aqueous zinc ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199419000000041
    Figure BDA0005199419000000041
  • Figure HDA0005199419010000011
    Figure HDA0005199419010000011
  • Figure HDA0005199419010000012
    Figure HDA0005199419010000012
Patent Text Reader

Abstract

The invention provides an application of an electrolyte containing xylenol orange tetrasodium salt in preparation of an aqueous zinc ion battery. The research on assembled symmetrical batteries shows that the aqueous zinc ion battery electrolyte containing the xylenol orange tetrasodium salt can circulate for more than 4000 hours under the charging and discharging conditions of 1mA cm <-2 > and 1mAh cm <-2 >; under the charging and discharging conditions of 5mA cm <-2 > and 5mAh cm <-2 >, the material can be cycled for more than 1000 hours; under the charging and discharging conditions of 0.5 mA cm <-2 > and 0.5 mAh cm <-2 >, circulation can be carried out for more than 1000 hours, so that the stability of the water-based zinc ion battery is effectively improved. In addition, the xylenol orange tetrasodium salt can promote uniform deposition of Zn < 2 + > on the surface of the zinc negative electrode, so that growth of zinc dendrites is effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to application of an electrolyte containing tetrasodium dimethyl orange to prepare aqueous zinc ion batteries. Background Art

[0002] Aqueous zinc-ion batteries refer to a new type of battery that uses water as a solvent and zinc ions as the main charge carrier. During its operation, zinc metal (Zn) releases electrons through a discharge reaction at the negative electrode of the battery, while zinc ions (Zn2+) migrate to the positive electrode in the electrolyte for a reduction reaction, completing the charge and discharge cycle of the secondary battery. Compared with traditional lithium-ion batteries, aqueous zinc-ion batteries (ZIBs) have high safety, low cost, high ionic conductivity, low redox potential (relative to the standard hydrogen electrode of -0.76V) and up to 820mAh g -1 The theoretical specific capacity of aqueous zinc-ion batteries has made them a promising competitor to replace lithium-ion batteries as large-scale energy storage systems. However, aqueous zinc-ion batteries face many intrinsic problems. For example, the protrusions on the zinc (Zn) negative electrode can trigger the tip effect, leading to the growth of zinc dendrites.

[0003] Among the many coping strategies, electrolyte design has been proven to be a simple and effective modification method. By introducing a small amount of additives to improve the stability of the electrode-electrolyte interface, it plays a role in adjusting the zinc ion deposition kinetics and diffusion, and greatly inhibits the growth of zinc dendrites. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, the present invention provides an electrolyte containing tetrasodium dimethyl phenol orange and a soluble zinc salt for inhibiting zinc dendrites in an aqueous zinc ion battery and improving the stability of the aqueous zinc ion battery.

[0005] An optional scheme is that the soluble zinc salt is at least one of zinc sulfate, zinc sulfate hydrate, zinc chloride, zinc chloride hydrate, zinc bromide, zinc bromide hydrate, zinc acetate, zinc acetate hydrate, zinc trifluoromethanesulfonate and zinc trifluoromethanesulfonate hydrate.

[0006] An optional solution is that the concentration of the soluble zinc salt in the electrolyte is 1.5-2.5 mol / L, and the concentration of tetrasodium xylenol orange is 0.5-2 mmol / L. Preferably, the concentration of the soluble zinc salt is 2 mol / L, and the concentration of tetrasodium xylenol orange is 1.5 mmol / L.

[0007] The present invention also claims protection for an electrolyte containing tetrasodium dimethyl phenol orange and a soluble zinc salt.

[0008] The object of protection of the present invention also relates to an aqueous zinc battery, which comprises an electrolyte, a positive electrode, a negative electrode and a separator, wherein the electrolyte is an electrolyte containing tetrasodium dimethyl orange and a soluble zinc salt; the positive electrode is a manganese-based oxide, a vanadium-based oxide, a Prussian blue analog, a carbon felt or a graphite felt; and the negative electrode is zinc or a zinc alloy. Further optionally, the working density of the battery is 0.5 mA / cm 2 ~5mA / cm 2 .

[0009] The aqueous zinc ion battery using the electrolyte containing tetrasodium dimethyl orange (IND) of the present invention has a high conductivity at 1 mA cm -2 , 1mAh cm -2 The charge and discharge conditions can be cycled for more than 4000 hours; at 5 mA cm -2 , 5mAh cm -2 The charge and discharge conditions can be cycled for more than 1000 hours; at 0.5 mA cm -2 , 0.5mAh cm -2 It can cycle for more than 1000 hours under the charging and discharging conditions, thus effectively improving the stability of the aqueous zinc-ion battery.

[0010] IND can make Zn 2+ Rapidly diffuse on the negative electrode surface to form a uniform deposition flow, thereby inhibiting the growth of zinc dendrites. At the same time, the hydroxyl groups can react with H 2 O produces hydrogen bonding, limiting the active H 2 O migrates to the negative electrode interface, thereby inhibiting the occurrence of hydrogen evolution corrosion reaction.

[0011] The life of the symmetrical battery made by preparing the electrolyte with the organic molecule tetrasodium salt of dimethyl phenol orange containing carboxyl and hydroxyl groups in the present application is significantly enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The Zn||Zn symmetric cell assembled for Example 3 is distributed at 1 mA cm -2 Time-voltage comparison curve of constant current charge and discharge test under current density.

[0013] Figure 2 The symmetric cell was assembled with sulfamic acid as an electrolyte additive at 1 mA cm -2 , 1mAh·cm -2 Charge and discharge test diagram under conditions.

[0014] Figure 3 1,3-Propanediamine-N,N,N,N-tetraacetic acid was used as an electrolyte additive to assemble a symmetrical cell at 1 mA·cm -2 , 1mAh·cm -2Charge and discharge test diagram under conditions.

[0015] Figure 4 Gallic acid was used as an electrolyte additive to assemble a symmetrical cell at 1 mA cm -2 , 1mAh·cm -2 Charge and discharge test diagram under conditions.

[0016] Figure 5 Caffeic acid was used as an electrolyte additive to assemble a symmetrical cell at 1 mA cm -2 , 1mAh·cm -2 Charge and discharge test diagram under conditions.

[0017] Figure 6 N-tris(hydroxymethyl)methylamino-2-hydroxypropanesulfonic acid was used as an electrolyte additive to assemble a symmetrical cell at 1 mA·cm -2 , 1mAh·cm -2 Charge and discharge test diagram under conditions.

[0018] Figure 7 The symmetrical battery assembled in Example 3 is 0.5 mA·cm -2 , 0.5mAh·cm -2 Charge and discharge test diagram under conditions.

[0019] Figure 8 The symmetrical battery assembled in Example 3 is 5 mA·cm -2 , 5mAh·cm -2 Charge and discharge test diagram under conditions.

[0020] Fig. 9 Coulombic efficiency of Zn||Cu half-cells tested in different electrolyte formulations at a current density of 1 mA cm -2 The cut-off charging voltage is 0.5V.

[0021] Fig.10 These are optical microscopic images of in-situ observation of zinc deposition using an optical microscope; Figure A is an optical microscopic image of zinc deposition of ZS, and Figure B is an optical microscopic image of zinc deposition of ZS+1.0IND of Example 2.

[0022] Fig.11 This is a chronoamperometry test diagram of the symmetrical battery assembled in Example 3.

[0023] Fig.12 This is a comparison chart of the zinc ion full battery cycle performance in Example 3. DETAILED DESCRIPTION

[0024] Unless otherwise specified, the scientific and technical terms used herein are understood according to the knowledge of ordinary technicians in the relevant fields.

[0025] The aqueous zinc ion battery of the present invention is different from the existing aqueous zinc ion battery in that the electrolyte of the aqueous zinc ion battery of the present invention contains tetrasodium dimethyl phenol orange (whose structural formula is shown in Formula 1), and the requirements and design methods of the battery structure, working parameters, etc. can all adopt existing related technologies.

[0026]

[0027] The present invention is further described below in conjunction with specific examples and comparative examples. The raw materials used in the following examples are all commercially available products.

[0028] Embodiment 1:

[0029] At room temperature, 11.48 g of zinc sulfate heptahydrate powder was added to 20 mL of deionized water and stirred continuously until the solution was clear to obtain a 2 mol / L basic zinc sulfate electrolyte (abbreviated as ZS);

[0030] Add tetrasodium xylenol orange powder (IND) to the zinc sulfate electrolyte, stir magnetically until the powder is completely dissolved, and allow to stand to obtain a stable electrolyte containing organic molecular additives of carboxyl and hydroxyl groups (abbreviated as ZS+0.5IND), wherein the concentration of tetrasodium xylenol orange in the electrolyte is 0.5 mmol / L.

[0031] Embodiment 2:

[0032] This embodiment is different from Embodiment 1 in that tetrasodium xylenol orange powder (IND) is added to the basic zinc sulfate electrolyte, and magnetic stirring is performed until the powder is completely dissolved. After standing, a stable electrolyte containing organic molecular additives of carboxyl and hydroxyl groups (abbreviated as ZS+1.0IND) is obtained, wherein the concentration of tetrasodium xylenol orange in the electrolyte is 1 mmol / L.

[0033] Embodiment 3:

[0034] This embodiment is different from Embodiment 1 in that tetrasodium xylenol orange powder (IND) is added to the basic zinc sulfate electrolyte, and magnetic stirring is performed until the powder is completely dissolved. After standing, a stable electrolyte containing organic molecular additives of carboxyl and hydroxyl groups (abbreviated as ZS+1.5IND) is obtained, wherein the concentration of tetrasodium xylenol orange in the electrolyte is 1.5 mmol / L.

[0035] Embodiment 4:

[0036] This embodiment is different from Embodiment 1 in that tetrasodium xylenol orange powder (IND) is added to the basic zinc sulfate electrolyte, and magnetic stirring is performed until the powder is completely dissolved. After standing, a stable electrolyte containing organic molecular additives of carboxyl and hydroxyl groups (abbreviated as ZS+2IND) is obtained, wherein the concentration of tetrasodium xylenol orange in the electrolyte is 2 mmol / L.

[0037] Comparative Example 1:

[0038] This embodiment is different from Embodiment 1 in that sulfamic acid powder is added to the basic zinc sulfate electrolyte, magnetic stirring is performed until the powder is completely dissolved, and a stable electrolyte is obtained after standing, wherein the concentration of sulfamic acid in the electrolyte is 1.5 mmol / L.

[0039] Comparative Example 2:

[0040] This embodiment is different from Embodiment 1 in that 1,3-propylenediamine-N,N,N,N-tetraacetic acid powder is added to the basic zinc sulfate electrolyte, and magnetic stirring is performed until the powder is completely dissolved. A stable electrolyte is obtained after standing, wherein the concentration of 1,3-propylenediamine-N,N,N,N-tetraacetic acid in the electrolyte is 1.5 mmol / L.

[0041] Comparative Example 3:

[0042] This embodiment is different from Embodiment 1 in that gallic acid powder is added to the basic zinc sulfate electrolyte, magnetic stirring is performed until the powder is completely dissolved, and a stable electrolyte is obtained after standing, wherein the concentration of gallic acid in the electrolyte is 1.5 mmol / L.

[0043] Comparative Example 4:

[0044] This embodiment is different from Embodiment 1 in that caffeic acid powder is added to the basic zinc sulfate electrolyte, magnetic stirring is performed until the powder is completely dissolved, and a stable electrolyte is obtained after standing, wherein the concentration of caffeic acid in the electrolyte is 1.5 mmol / L.

[0045] Comparative Example 5:

[0046] This embodiment is different from Example 1 in that N-tris(hydroxymethyl)methylamino-2-hydroxypropanesulfonic acid powder is added to the basic zinc sulfate electrolyte, magnetic stirring is performed until the powder is completely dissolved, and a stable electrolyte is obtained after standing, wherein the concentration of N-tris(hydroxymethyl)methylamino-2-hydroxypropanesulfonic acid in the electrolyte is 1.5 mmol / L.

[0047] Furthermore, the electrolytes prepared in the above Example 2 and Comparative Examples 1-5 were subjected to constant current charge and discharge performance tests:

[0048] Commercial zinc foil (1cm 2 ) as the negative electrode and the electrolytes obtained in Example 3 and Comparative Examples 1-5 were assembled into symmetrical batteries, and constant current charge and discharge tests were performed. The test was performed at 1 mA·cm -2The current density is discharged for 1 hour and then charged for 1 hour, and then the cycle is carried out. During the process, the current density and the size of the charge and discharge capacity are adjusted by the charge and discharge equipment through control. The time voltage comparison curve of the constant current charge and discharge test is as follows Figure 1-Figure 7 shown.

[0049] Depend on Figure 1 It can be seen that the electrolyte of Example 3 exhibits a long cycle life and excellent voltage stability. -2 Current density, 1 mAh cm -2 The battery can be stably cycled for ≥4000h at a charge-discharge capacity of 10000 h. The basic zinc sulfate electrolyte exhibits poor cycle stability and life. -2 Current density, 1 mAh cm -2 The charge and discharge capacity of the battery can only be cycled for less than 200 hours.

[0050] Depend on Figure 7 It can be seen that at 0.5 mA cm -2 The current density is 0.5 mAh cm -2 The electrolyte of Example 3 can stably cycle for ≥1000h under the charge and discharge capacity of Figure 8 It can be seen that at 5 mA cm -2 The current density is 5 mAh cm -2 The electrolyte of Example 2 can stably cycle for ≥1000 h at a charge-discharge capacity of . Therefore, the symmetrical battery prepared by the electrolyte containing tetrasodium salt of xylenol orange additive obtained in Example 3 has a long cycle life and excellent voltage stability.

[0051] The time voltage curves of the constant current charge and discharge tests of Comparative Examples 1-5 are as follows: Figures 2 to 6 As shown in the figure, the symmetrical battery assembled with the electrolyte obtained by commercial zinc foil in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5 has a conductivity of 1 mA·cm -2 Current density, 1 mAh cm -2 After cycling for 200h, 300h, 1600h, 1500h and 1000h at the charge and discharge capacity of the battery, a short circuit occurred.

[0052] Further, the coulombic efficiency test was performed on the electrolyte of Example 3:

[0053] Commercial zinc foil (1 cm2) was used as the negative electrode and assembled into a Zn||Cu half-cell with the 2 mol / L zinc sulfate electrolyte obtained in Example 3 and the electrolyte containing tetrasodium dimethyl orange, and the coulombic efficiency was tested. The test was carried out at 1 mA·cm -2 Discharged for 1 h at a current density of 1 mA·cm -2The current density is charged to 0.5V, and then cycled, such as Fig. 9 shown.

[0054] Depend on Fig. 9 It can be seen that the commercial zinc foil exhibited a long cycle number and a high coulombic efficiency retention rate in the electrolyte containing tetrasodium dimethyl phenol orange obtained in Example 3, and was able to stably cycle 4000 times with the coulombic efficiency maintained at 99%. However, the commercial zinc foil exhibited poor cycle stability and coulombic efficiency in the 2 mol / L zinc sulfate electrolyte obtained in Example 3.

[0055] The following is the performance analysis of the electroplating (inhibiting zinc dendrite formation) of the electrolyte of Example 3:

[0056] Select Zn sheet (1cm 2 ) as current collector and placed in electrolyte (basic electrolyte ZS and ZS+1.0IND electrolyte) for zinc electrodeposition. The zinc deposition was observed in situ with an optical microscope and compared with the two. Fig.10 As can be seen from Figure B, the electrolyte containing tetrasodium dimethyl orange has no obvious bubbles during the deposition process, reflecting that the hydrogen evolution reaction is not obvious during the zinc deposition process; while the zinc sulfate solution in Figure A is the opposite of the present invention, further reflecting that the present invention effectively inhibits side reactions.

[0057] Zinc sheet (1cm 2 ) (size) as the negative electrode, ZS+1.5IND and ZS in Example 3 were used to assemble symmetrical batteries and perform chronoamperometry tests:

[0058] The chronoamperometric test showed that the zinc ions diffused faster in the ZS+1.5IND of Example 3. The specific results are shown in Fig.11 .

[0059] Zinc vanadate was used as the positive electrode material. Zinc sheet (1cm 2 ) as the negative electrode, ZS+1.5IND and ZS in Example 3 were used to assemble full batteries, and relevant performance tests were performed:

[0060] Preparation method of zinc vanadate positive electrode:

[0061] 0.5 g of vanadium pentoxide was added to 7.7 ml of deionized water and 1.7 ml of hydrogen peroxide, stirred for 15 minutes, then 40 ml of deionized water was added, stirred evenly, and ultrasonicated for 2 hours; then 0.15 g of Zn(CH 3 COO 2 ·H 2 0, stirred for another 10 minutes, reacted at 180°C for 90 minutes, and then ultrasonically cleaned.

[0062] The prepared zinc vanadate powder and Surper P:PVDF in a ratio of 7:2:1 were mixed evenly and coated on graphite foil by scraping. The coated sheet was dried in a vacuum drying oven at 80°C overnight to obtain a positive electrode material sheet.

[0063] According to the positive electrode shell (2cm 2 )、ZnVanadate positive electrode sheet (1cm 2 )、Electrolyte sheet (glass fiber, 2cm 2 )、Negative electrode (zinc foil, 1cm 2 )、Spacer((2cm 2 )、shrapnel(2cm 2 )、Negative electrode shell (2cm 2 ) are assembled in sequence to obtain a zinc full-ion battery (wherein the electrode shell, gasket and shrapnel are all 2032 type and made of stainless steel).

[0064] The cycle performance of the zinc ion full battery was tested, and the specific results are shown in Fig.12 , Fig.12 It shows that the capacity attenuation of the full battery using ZS electrolyte is more serious; in contrast, the full battery using ZS+1.5IND electrolyte can be stably cycled for up to 2000 times. The results show that the present invention significantly improves the stability of the Zn anode.

[0065] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the technical content disclosed above, or modify it into an equivalent embodiment with equivalent changes without departing from the scope of the technical solution of the present invention. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should fall within the scope of protection of the technical solution of the present invention.

Claims

1. Application of an electrolyte containing tetrasodium dimethyl orange and a soluble zinc salt for inhibiting zinc dendrites in an aqueous zinc ion battery and improving the stability of the aqueous zinc ion battery.

2. The use according to claim 1, characterized in that: The soluble zinc salt is at least one of zinc sulfate, zinc sulfate hydrate, zinc chloride, zinc chloride hydrate, zinc bromide, zinc bromide hydrate, zinc acetate, zinc acetate hydrate, zinc trifluoromethanesulfonate and zinc trifluoromethanesulfonate hydrate.

3. The use according to claim 1, characterized in that: The concentration of the soluble zinc salt in the electrolyte is 1.5-2.5 mol / L; the concentration of the tetrasodium salt of xylenol orange is 0.5-2 mmol / L.

4. An electrolyte containing tetrasodium dimethyl orange and a soluble zinc salt.

5. An aqueous zinc battery, comprising an electrolyte, a positive electrode, a negative electrode and a separator, characterized in that: The electrolyte is an electrolyte containing tetrasodium dimethyl orange and a soluble zinc salt; the positive electrode is a manganese-based oxide, a vanadium-based oxide, a Prussian blue analog, a carbon felt or a graphite felt; and the negative electrode is zinc or a zinc alloy.

6. The aqueous zinc battery according to claim 5, characterized in that: The working density of the battery is 0.5 mA / cm 2 ~5mA / cm 2 .